1986
DOI: 10.1097/00006842-198607000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed anger and blood pressure: the effects of race, sex, social class, obesity, and age.

Abstract: We studied 572 men and women who participated in a blood pressure screening program at a government unemployment office. Before having their blood pressures taken, the subjects completed a brief questionnaire that included two items measuring conflict over anger expression. Information was also obtained on obesity, race, sex, social class, and age. Across all subjects, systolic blood pressure was found to be significantly related to suppressed anger (p less than 0.016). Normotensive were twice as likely as hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
2
3

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(44 citation statements)
references
References 0 publications
2
37
2
3
Order By: Relevance
“…In contrast, individuals scoring high in alexithymia are more frequent users of suppression and, therefore, more likely to have developed overtrained schemata of efficient suppression techniques, increasing thereby their chances of success when using suppression. This explanation is consistent with previous research indicating that alexithymia scores are linked to a more frequent utilization of suppression techniques (e.g., Dimsdale et al, 1986;Franz et al, 2004;Grabe et al, 2004;Kessler et al, 2010;Richter et al, 2006;Swart et al, 2009). This explanation is also consistent with research suggesting that long-term expertise in regulation techniques improves efficiency in controlling emotional responses (Dalgleish, Yiend, Schweizer, & Dunn, 2009;Wegner & Gold, 1995).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, individuals scoring high in alexithymia are more frequent users of suppression and, therefore, more likely to have developed overtrained schemata of efficient suppression techniques, increasing thereby their chances of success when using suppression. This explanation is consistent with previous research indicating that alexithymia scores are linked to a more frequent utilization of suppression techniques (e.g., Dimsdale et al, 1986;Franz et al, 2004;Grabe et al, 2004;Kessler et al, 2010;Richter et al, 2006;Swart et al, 2009). This explanation is also consistent with research suggesting that long-term expertise in regulation techniques improves efficiency in controlling emotional responses (Dalgleish, Yiend, Schweizer, & Dunn, 2009;Wegner & Gold, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…Alexithymia is a trait in which individuals have a reduced ability to regulate, identify, and communicate feelings or emotions (Franz, Schaefer, Schneider, Sitte, & Bachor, 2004;Sifneos, 1973). Importantly, alexithymia seems to be characterized by an emotion regulation style overreliant on suppression, rather than reappraisal, strategies (e.g., Dimsdale et al, 1986;Franz et al, 2004;Grabe et al, 2004;Kessler, Kammerer, Hoffmann, & Traue, 2010;Richter et al, 2006;Swart, Kortekaas, & Aleman, 2009). For instance, Kessler et al found a positive relationship between TAS scores and individual differences in expressive suppression.…”
Section: Introductionmentioning
confidence: 99%
“…As dislipidemias são causas fundamentais de doenças coronarianas ateroscleróticas 1,7,8,10,16,30,32,34 . A prevenção dessas morbidades e dos fatores de risco, que se apresentem como determinantes ou associados às mesmas, tem aumentado consideravelmente a esperança de vida de grupos populacionais em fase produtiva, principalmente de países desenvolvidos, onde há muito se realizam pesquisas epidemiológicas, pelos estudos longitudinais e transversais, seguidas da aplicação de programas de intervenção 15,19,21 .…”
unclassified
“…Behaviour and the human mind, however, cannot be adequately understood without an appreciation of the pivotal role played by anger. Studies have examined the relation of anger with hypertension and cardiac diseases [1][2][3][4][5][6][7][8][9][10][11][12][13][14], eating disorders [15][16][17][18][19][20][21][22][23][24][25], and personality disorders [26, pp 20-21; 27, pp 267-268], as well as many other psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%